Prospects for Services Trade Negotiations - Jeffrey J. Schott; Minsoo Lee; Julia Muir (Asian Development Bank (ADB), 2012)
Trade and investment in services are difficult to measure, and the regulatory barriers that inhibit the free flow of services are hard to quantify. As a result, very little attention has been paid to dismantling barriers to services trade and investment. Rather, free trade negotiations tend to focus on liberalizing merchandise trade. This paper examines what has been achieved in both regional and multilateral compacts by surveying international precedents involving Asian countries in which services reforms have been included in bilateral and regional trade pacts. We then assess the prospects for services trade negotiations and explore how services trade negotiations could be pursued over the next decade through two distinct channels: the Trans-Pacific Partnership and a plurilateral approach among groups of World Trade Organization countries. We find that in the case of developing Asia, free trade agreements have largely excluded services or have only committed to "lock in" current practices in a narrow subset of service sectors. This is also the case in agreements negotiated between developing countries, which have produced less substantial commitments to liberalize services than those negotiated between developing and developed countries. Multilateral negotiations on services have also underperformed, as substantive negotiations on services in the Doha Round never really got underway. To that end, we advocate a stronger effort by developing Asian countries to prioritize services negotiations in their regional arrangements, and to expand coverage of services in those pacts to a broad range of infrastructure services that are included in other free trade agreements in force or under construction in Asia and the Pacific region.
hdl:11540/1264
Keywords: 330; Dienstleistungshandel; Handelsabkommen; WTO-Recht; Asien